PERAN KOMPETENSI DAN JOB DESIGN TERHADAP KINERJA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA PENDAMPING PROGAM KELUARGA HARAPAN KABUPATEN GRESIK - Nabella Wahyuning Suwarno; Yanuar Fauzuddin (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2024)
The purpose of this study was to find out and test the role of competence and job design on performance with organizational commitment as an intervening variable in the Families of Hope Program assistant in Gresik Regency. This research is a type of quantitative research using a sample of 60 people with the Proportional Stratified Random Sampling method based on predetermined criteria. Collecting research data using a questionnaire. This study uses Smart-PLS, namely the statistical method of Structural Equation Model (SEM). The results of this study indicate that competence has a positive and significant effect on organizational commitment, Job design has a positive and significant effect on organizational commitment, Competence has a negative and significant effect on assistant performance, Job design has a positive and significant effect on assistant performance, Organizational commitment has a positive and significant effect on performance companion, organizational commitment mediates the effect of competence on the performance of the assistant and mediates the influence of job design on the performance of the assistant for the Family Hope Program, Gresik Regency.